À la croisée des univers du transmedia, de la marque et de la franchise dans l’industrie cinématographique - Hélène Laurichesse (Mise au Point)
The escalation of brand strategy and transmedia narratives in the creative industries drove us to focus on the interaction between these two trends consistently associated in the previous studies. Are they actually independent or interrelated? We will show that branding in the motion picture industry doesn’t necessarily take a transmedia form, but the transmedia narrative is the more obvious and achieved way to build a brand. We will define the transmedia franchise and examine its commercial side. By generating additional revenues beyond traditional forms of exploitation, the franchise now embodies the economic model leading to financial performance. Box-office analysis will allow us to evaluate this efficiency based on a panel of 126 franchises source studies.